2014
DOI: 10.1259/bjr.20140374
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity focused ultrasound ablation: an effective and safe treatment for secondary hypersplenism

Abstract: Objective: Hypersplenism is a common disease. The conventional treatment is splenectomy and partial splenic embolization; however, both of them have high complication rates and technical defects. Therefore, safer and more effective techniques should be considered for the treatment of hypersplenism. High-intensity focused ultrasound (HIFU) may provide an effective and safe way for treatment of hypersplenism. Therefore, we conducted this study to assess the safety and efficacy of HIFU in treatment of secondary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Recently, investigators also aimed to use HIFU for the treatment of other diseases, such as secondary hypersplenism. Previous studies have investigated the safety and efficacy of HIFU in the treatment of secondary hypersplenism caused by cirrhosis 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, investigators also aimed to use HIFU for the treatment of other diseases, such as secondary hypersplenism. Previous studies have investigated the safety and efficacy of HIFU in the treatment of secondary hypersplenism caused by cirrhosis 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This result is in accordance with those of previous studies. Zhu et al 7 reported that HIFU is safe and effective in the treatment of cirrhotic secondary hypersplenism in patients whose liver function is classified as Child–Pugh A or B. No major complications, such as gastrointestinal perforation, peritonitis, splenic rupture or abscess, occurred peri-HIFU and/or post-HIFU.…”
Section: Discussionmentioning
confidence: 99%
“…Microwave ablation can improve hypersplenism in cirrhosis patients, but multiple ablations are required, with mean ablation times of 8.8 ± 1.3, and the therapeutic effect is not as good as splenectomy [45]. Although high-intensity focused ultrasound improved hypersplenism, both white blood cells (WBCs) and platelet counts did not return to normal levels [46]. Studies have shown that in children with chronic liver disease with hypersplenism [47] and cirrhosis in adults [48], after propranolol treatment for 1-4 weeks, platelet counts significantly increase.…”
Section: Discussionmentioning
confidence: 99%
“…Focused ultrasound therapy might be further developed by controlling the local heating phenomena 31 . With the expansion of the indications for HIFU, it has been applied to many nontumor diseases, such as uterine fibroids and hypersplenism, 11 13 and it could offer a safer treatment option for clinical hypersplenism.…”
Section: Discussionmentioning
confidence: 99%
“…Liangpunsakul et al 1 reported that 70% to 80% of cirrhotic patients with portal hypertension had different degrees of splenomegaly and hypersplenism. Hypersplenism has diverse treatments, including drug therapy; surgical splenectomy; percutaneous injections 2 ; thermal ablation, such as radiofrequency ablation, 3 7 microwave ablation, 8 – 10 and high‐intensity focused ultrasound (HIFU) 11 13 ; and even radiotherapy 14 16 . Splenectomy is the traditional therapy of choice when patients with hypersplenism are symptomatic, with bleeding disorders or hemolytic anemia 17 .…”
mentioning
confidence: 99%